Airasia in the Malaysian domestic airline market: empirical analysis of strategy - Mok, Kim Man; Jainurin Justine (Clute Institute, 2005)
This paper will examine the results of the strategic actions of AirAsia in the Malaysian domestic airline market. Firstly, the paper will provide a general background of the airline industry, in particular the Malaysian domestic airline market and a summary of an analysis of the industry using Michael Porter’s Five Forces Analysis. Secondly, the paper will provide a brief background of AirAsia and Malaysia Airlines. Thirdly, the paper will analyse the results of AirAsia’s strategy vis-à-vis operating and financial performance. Finally, the paper will conclude a summary of AirAsia’s achievement of the past and present and prospect for the future.